Plant epigenetics: from genotype to phenotype and back again. Issue 1 (December 2016) - Slotkin, R.
Abstract A report on thePlant Epigenetics: From Genotype to Phenotype Keystone Symposium held in Taos, New Mexico, USA, 15–19 February, 2016.